1999
DOI: 10.1080/13625189909040808
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance to activated protein C and factor V Leiden in recurrent abortions. Review of other hypercoagulability factors

Abstract: Increased activated protein C resistance appears to be an important factor in women with recurrent abortions. These data indicate the need for routine investigation of activated protein C resistance in women with recurrent abortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
10
1
2
Order By: Relevance
“…However, Factor V H1299R is associated with inherited mild-activated protein C resistance but mainly in homozygous state and predisposing to thrombosis. Factor V Leiden, responsible for more than 75% of inherited activated protein C resistance, is a common inherited thrombotic risk factor and there are conflicting results about but its association with spontaneous abortions especially early in pregnancy is controversial (Brenner, 1999;Brenner et al, 1999;Hatzis et al, 1999;Tranquilli et al, 2004;Coulam et al, 2006;Rodger et al, 2010). Its prevalence in our study was higher in women than in men (2.8% and 2.4%), but not statistically significant.…”
Section: Discussioncontrasting
confidence: 34%
“…However, Factor V H1299R is associated with inherited mild-activated protein C resistance but mainly in homozygous state and predisposing to thrombosis. Factor V Leiden, responsible for more than 75% of inherited activated protein C resistance, is a common inherited thrombotic risk factor and there are conflicting results about but its association with spontaneous abortions especially early in pregnancy is controversial (Brenner, 1999;Brenner et al, 1999;Hatzis et al, 1999;Tranquilli et al, 2004;Coulam et al, 2006;Rodger et al, 2010). Its prevalence in our study was higher in women than in men (2.8% and 2.4%), but not statistically significant.…”
Section: Discussioncontrasting
confidence: 34%
“…Another study demonstrated a fetal loss of between 28 to 32% in women with antithrombin III deficiency compared with 23 % in unaffected controls (Sanson et al, 1996). However no significant association between antithrombin deficiency and recurrent loss was found in other studies (Hatzis et al, 1999;Roque et al, 2004;Folkeringa et al, 2007). A Spanish retrospective study found 56% of women with antithrombin deficiency had an adverse pregnancy outcome (Robertson et al, 2006).…”
Section: Antithrombin Deficiencymentioning
confidence: 99%
“…58,61,62 The ORs for elevated anticardiolipin antibodies and lupus anticoagulants were 3.40 and 2.97, respectively. [63][64][65][66][67][68][69] However, pooled data on lupus anticoagulants indicated significant heterogeneity (p = 0.04). Sensitivity analysis was performed.…”
Section: Early Pregnancy Lossmentioning
confidence: 99%